2019
DOI: 10.1155/2019/8980794
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Fluid Inclusion and Stable Isotope Analysis on Deep Carbonates from the North Alpine Foreland Basin to Constrain Paleofluid Evolution

Abstract: The recent interest on environmentally friendly energy resources has increased the economic interest on the Upper Jurassic carbonate rocks in the North Alpine Foreland Basin, which serves as a hydrogeothermal reservoir. An economic reservoir use by geothermal fluid extraction and injection requires a decent understanding of porosity–permeability evolution of the deep laying Upper Jurassic strata at depths greater than 2000 m. The analysis of paleofluids caught in cements of the rock mass helps to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 41 publications
(58 reference statements)
3
43
0
Order By: Relevance
“…Geothermal exploration results show that faults, depositional facies, karst, diagenesis and dolomitisation control porosity, permeability and hence reservoir productivity (Dussel et al, 2016;Mraz et al, 2019), which has also been shown for carbonates in the Alberta Basin (Drivet & Mountjoy, 1997;Mountjoy et al, 2001).…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Geothermal exploration results show that faults, depositional facies, karst, diagenesis and dolomitisation control porosity, permeability and hence reservoir productivity (Dussel et al, 2016;Mraz et al, 2019), which has also been shown for carbonates in the Alberta Basin (Drivet & Mountjoy, 1997;Mountjoy et al, 2001).…”
Section: Discussionmentioning
confidence: 63%
“…Ingebritsen & Manning, 1999;Ehrenberg & Nadeau, 2005;Stober & Bucher, 2007, 2015Stober, 2011), and most likely diagenetic processes such as pressure solution and precipitation might impair porosity and permeability with depth. Mraz et al (2019) show in an extensive study of the Upper Jurassic in the Molasse Basin that depth-related processes, notably compaction and diagenesis, have a significant effect on porosity and reservoir productivity. Certain facies types such as reef or reef detritus become less relevant for reservoir production while compaction and diagenesis come to control permeability variability with depth (Mraz et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations